2014
DOI: 10.1007/s11011-014-9507-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of functional connectivity, working memory and inhibitory control on multi-modal brain MR imaging with Rifaximin in Cirrhosis: Implications for the gut-liver-brain axis

Abstract: Objective Minimal hepatic encephalopathy (MHE) impairs daily functioning in cirrhosis, but its functional brain impact is not completely understood. Aim To evaluate the effect of rifaximin, a gut-specific antibiotic, on the gut-liver-brain axis in MHE. Hypothesis Rifaximin will reduce endotoxemia, enhance cognition, increase activation during working memory(N-back) and reduce activation needed for inhibitory control tasks. Methods Cirrhotics with MHE underwent baseline endotoxin and cognitive testing, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 39 publications
1
65
0
Order By: Relevance
“…20 Non-microbial studies using lactulose, probiotics, and rifaximin in MHE patients have shown varying degrees of cognitive improvement, reduction in endotoxemia, decreased brain swelling, and enhanced connectivity on multimodal MRI. [21][22][23][24] A systematic study of MHE therapy with rifaximin was performed by our group in which we found a significant improvement in cognitive performance. 25 This was accompanied by an enhanced working memory performance via facilitation of the functioning of subcortical structures, greater inhibitory control by modulation of fronto-parietal activation, and improved white matter integrity in MHE after rifaximin on multi-modal brain MR imaging.…”
Section: Mhe Therapymentioning
confidence: 85%
See 1 more Smart Citation
“…20 Non-microbial studies using lactulose, probiotics, and rifaximin in MHE patients have shown varying degrees of cognitive improvement, reduction in endotoxemia, decreased brain swelling, and enhanced connectivity on multimodal MRI. [21][22][23][24] A systematic study of MHE therapy with rifaximin was performed by our group in which we found a significant improvement in cognitive performance. 25 This was accompanied by an enhanced working memory performance via facilitation of the functioning of subcortical structures, greater inhibitory control by modulation of fronto-parietal activation, and improved white matter integrity in MHE after rifaximin on multi-modal brain MR imaging.…”
Section: Mhe Therapymentioning
confidence: 85%
“…We also found improved neural network connectivity between frontal and parietal structures and, in particular, facilitation of the left parietal operculum. 26 However, despite these improvements and a reduction in endotoxemia after rifaximin, there was only a modest effect on relative bacterial abundance. This, however, was in line with prior studies in settings independent of cirrhosis in which a significant change in bacterial virulence and behavior rather than change in number with rifaximin were noted.…”
Section: Mhe Therapymentioning
confidence: 99%
“…For example, maternal separation, restraint conditions, crowding, heat stress, and acoustic stress all alter the composition of the gut microbiota (Bailey et al, 2011;De Palma et al, 2014;Moloney et al, 2014). In addition, a growing body of data suggests that the microbiota may be involved in controlling behaviors relevant to stress-related disorders.…”
Section: Introductionmentioning
confidence: 99%
“…However, future studies which include concurrent functional MRI sequences (Ahluwalia et al, 2014) may also shed further light on the meaning and context of the changes observed with MTR and DWI.…”
Section: Discussionmentioning
confidence: 99%
“…However, future studies which include concurrent functional MRI sequences (Ahluwalia et al, 2014) Abbreviations: PoA= power of attention, CoA= continuity of attention, QoEM= quality of episodic memory, QoWM= quality of working memory, SoM= speed of memory *Z scores represent the number and direction of standard deviations in the patient data compared to those from the healthy controls ** Psychometric performance was classified as impaired if the total Z score for all domains was  -3 *significance value between healthy controls and the patient entire population with cirrhosis, corrected for multiple comparisons; ****** = p<0.0001;*** = p<0.005; * = p<0.05; NS = non-significant. There were no significant differences between the neuropsychometrically unimpaired and the neuropsychometrically impaired patients …”
Section: Discussionmentioning
confidence: 99%